2014
DOI: 10.1099/vir.0.060269-0
|View full text |Cite
|
Sign up to set email alerts
|

The asparagine residue in the FRNK box of potyviral helper-component protease is critical for its small RNA binding and subcellular localization

Abstract: The multifunctional potyviral helper-component protease (HcPro) transgenic plants more than HcPro did, suggesting that replacement of asparagine in the FRNK box favours RNA silencing suppression. HcPro was found to be distributed in the nucleus and cytoplasm, whereas HcPro N182L was observed only in cytoplasmic inclusion bodies in N.benthamiana leaves, when fused to a GFP tag and expressed by agro-infiltration, suggesting mutation favours oligomerization of HcPro. These findings suggest that amino acid N 182… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…HC-Pro was one of the first two viral suppressors of RNA silencing to be identified, the other being the 2b counter-defense protein of Cucumber mosaic virus (CMV) (Anandalakshmi et al, 1998;Brigneti et al, 1998;Kasschau & Carrington, 1998). The HC-Pro factors of potyviruses inhibit antiviral RNA silencing through binding of 21 nucleotide shortinterfering RNAs and also acts as symptom determinants through interactions with, among other things, Argonaute factors, calmodulin-like factors, and the proteasome (Anandalakshmi et al, 2000;Nakahara et al, 2012;Sahana et al, 2014;Shiboleth et al, 2007). So far, cellular proteins interacting with the HC-Pro or P1/HC-Pro factors of BCMV and BCMNV remain unidentified.…”
Section: Infection and Symptomsmentioning
confidence: 97%
See 1 more Smart Citation
“…HC-Pro was one of the first two viral suppressors of RNA silencing to be identified, the other being the 2b counter-defense protein of Cucumber mosaic virus (CMV) (Anandalakshmi et al, 1998;Brigneti et al, 1998;Kasschau & Carrington, 1998). The HC-Pro factors of potyviruses inhibit antiviral RNA silencing through binding of 21 nucleotide shortinterfering RNAs and also acts as symptom determinants through interactions with, among other things, Argonaute factors, calmodulin-like factors, and the proteasome (Anandalakshmi et al, 2000;Nakahara et al, 2012;Sahana et al, 2014;Shiboleth et al, 2007). So far, cellular proteins interacting with the HC-Pro or P1/HC-Pro factors of BCMV and BCMNV remain unidentified.…”
Section: Infection and Symptomsmentioning
confidence: 97%
“…Domain II is involved in genome amplification predominantly through suppression of RNA silencing. Domain II contains the IGN motif and the FRNK box, which are crucial for RNA-silencing suppression and efficient viral RNA accumulation (Kasschau et al, 1997;Sahana et al, 2014;Shiboleth et al, 2007). Domain III is also involved in cell-to-cell movement as well as possessing proteinase activity for polyprotein processing (Hasiów-Jaroszewska et al, 2014).…”
Section: Infection and Symptomsmentioning
confidence: 99%
“…Previous studies indicated that potyviral HC-Pros were distributed to the cytoplasm (Riedel et al, 1998;Mlotshwa et al, 2002;Zheng et al, 2011;Sahana et al, 2014), nucleus (Riedel et al, 1998;Sahana et al, 2014), cytoplasm filaments, cell membrane, or nuclear envelope (Zheng et al, 2011). In addition, Turnip mosaic virus HC-Pro and Potato virus Y (PVY) HC-Pro could form aggregates in the cytoplasm (Zheng et al, 2011;del Toro et al, 2014), and an amino acid change of Papaya ringspot virus HC-Pro also led to the formation of the aggregates (Sahana et al, 2014). Interestingly, PVY HC-Pro also could be present in the chloroplasts of PVY-infected plants (Gunasinghe and Berger, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was demonstrated that Potato virus A HC-Pro induced the formation of RNA granules and localized abundantly there, which played an important role in virus infection (Hafrén et al, 2015). Point mutations that compromised the RSS activity of Potato virus A HC-Pro concomitantly abolished its ability to generate the RNA granules (Hafrén et al, 2015), and conversely, an amino acid substitution in Papaya ringspot virus HC-Pro that increased the formation of aggregate simultaneously increased the capacity of HC-Pro to suppress RNA silencing (Sahana et al, 2014). Han et al (2016) found that HC-Pro exhibited strong VSR activity and formed large subcellular aggregates by investigating three natural Turnip mosaic virus isolates.…”
Section: Zmvde Relocalized To Scmv Hc-pro-containing Aggregate Bodiesmentioning
confidence: 99%
“…Sahana et al (2014),Torres-Barcelo et al (2010), -Ruiz et al(2010),Torres-Barcelo et al (2008),Goto et al (2007),Shiboleth et al (2007),Yu et al (2006),Merai et al (2006),Dunoyer et al (2004),Llave et al (2000),Mallory et al (2001),Lozsa et al (2008),Ebhardt et al (2005), Jamous et al (2011), Endres et al (2010), Zhang et al (2008), Seo et al (2010), Westwood et al (2014), Canizares et al (2013), Haikonen et al (2013a), Shen et al (2010), Cheng et al (2008), Jin et al (2007), Chapman et al (2004), Kasschau et al (2003), Soitamo et al et al (2012) and Giner et al (2010) CVYV P1b 21 and 22 nt siRNA binding, protease activity, putativ Znfinger Valli et al (2011) and Valli et al (2008) Tombus virus CymRSV, CIRV, TBSV P19 ds-sRNA binding, interfering with sRNA 3' methylation, mir168 upregulation mediated AGO1 downregulation, HR elicitor, Hin19 interaction, ALY interaction Law et al (2013), Rawlings et al (2011), Cheng et al (2009), Xia et al (2009), Koukiekoloa et al (2007), Merai et al (2006), Lakatos et al (2006), Omarov et al (2006), Havelda et al (2005), Dunoyer et al (2004), Silhavy et al (2002), Ye et al (2003), Vargason et al (2003), Lozsa et al (2008), Yu et al (2006), Chapman et al (2004), Varallyay et al (2010, 2014), Várallyay and Havelda (2013), Angel and Schoelz (2013), Hsieh et al (2009), Park et al (2004) and Uhrig et al 2 binding, DCL1 upregulation to antagonize DCL4 and DCL 3, dsRNA binding, blocking primary siRNA biogenesis by RAV2 interaction, TIP-interaction, DRB-HRT mediated HR elicitor, AGO1 downregulation via miR168 upregulation Azevedo et al (2010), Jin and Zhu (2010), Várallyay and Havelda (2013), Zhang J. et al (2012), Merai et al (2006), Endres et al (2010), Donze et al (2014), Choi et al (2004), Ren et al (2000), Zhu et al (2013, 2014), Jeong et al (2008) and Pérez-Cañamás and Hernández (2015) PFVB, HCRSV, PLPV P37 siRNA binding Martinez-Turino and Hernandez (2009), Meng et al (2006) and Pérez-Cañamás and Hernández (2015) MNSV P7B Unknown, movement Protein Genovés et al (2011) and Genoves et al (2006) MNSV P42 Unknown Genoves et al (2006) Diantho virus RCNMV replication Unknown (DCL1 dependent), miRNA pathway interference Takeda et al (2005) RCNMV MP Unknown Powers et al (2008) Clostero virus BYV P21 ds-sRNA binding, blocking HEN1 methyltransferase Merai et al (2006), Yu et al (2006), Reed et al (2003) and Chapman et al…”
mentioning
confidence: 97%